2022
DOI: 10.3390/su14137932
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Comparison of Wheat and Maize Seedlings Responses to Water Stresses

Abstract: The aim of the study was to investigate specific responses of spring wheat (C3 photosynthesis) and maize (C4 photosynthesis) to drought and flooding stress. Analyses of water content, gas exchange intensity, photosynthetic apparatus activity, chlorophyll content, plant height and biological membrane integrity were performed on the 10th day of drought and flooding in both species at the third leaf stage. A specific response of wheat under both drought and flooding conditions involved an increase in ETo/RC ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The ability to retain stability of cell membrane under drought stress is one of the key physiological indices widely used to evaluate the drought tolerance of plants 93 . Measurements of relative water content (RWC), water loss (WL), electrolyte leakage (EL), and photosynthetic water use efficiency (WUE) are parameters frequently used as a selection test for the assessment of plant cultivar tolerance to various stresses 94 97 .…”
Section: Resultsmentioning
confidence: 99%
“…The ability to retain stability of cell membrane under drought stress is one of the key physiological indices widely used to evaluate the drought tolerance of plants 93 . Measurements of relative water content (RWC), water loss (WL), electrolyte leakage (EL), and photosynthetic water use efficiency (WUE) are parameters frequently used as a selection test for the assessment of plant cultivar tolerance to various stresses 94 97 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that sorghum has a yield advantage over maize under dry field conditions [28,29], while flooding reduces the leaf area, plant height, and leaf expansion rate in maize [27,30] and sorghum [31][32][33] as well. Furthermore, it is well known that sorghum is less soil-sensitive than maize and that it can be grown in almost any type of soil [34].…”
Section: Introductionmentioning
confidence: 99%
“…By process-based crop models, Webber et al [ 22 ] predicted that drought will cause higher yield losses for maize than for wheat. Recently, Ostrowska and Hura [ 23 ] selected quick photosynthetical parameters for the evaluation of the reactions to water stress (including drought) of maize and wheat which are possessing C4 and C3 type of photosynthesis, respectively.…”
Section: Introductionmentioning
confidence: 99%